1994
DOI: 10.1111/j.1432-1033.1994.00893.x
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Human Glutathione S‐transferase GSTP1‐1 Isoforms with Isoleucine and Valine in Position 104 Differ in Enzymic Properties

Abstract: Glutathione S‐transferase P1‐1 isoforms, differing in a single amino acid residue (Ile104 or Val104), have been previously identified in human placenta [Ahmad, H., Wilson, D. E., Fritz, R. R., Singh, S. V., Medh, R. D., Nagle, G. T., Awasthi, Y. C. & Kurosky, A. (1990) Arch. Biochem. Biophys. 278, 398–408]. In the present report, the enzymic properties of these two proteins are compared. [I104]glutathione S‐transferase P1‐1 has been expressed from its cDNA in Escherichia coli and purified to homogeneity by aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
269
1
7

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(289 citation statements)
references
References 41 publications
12
269
1
7
Order By: Relevance
“…These results are similar to those in a previous report in which a recombinant GSTP1b-1b protein expressed from a cDNA obtained artificially by site-directed mutagenesis of hGSTP1*A, was shown to have a 4-fold higher K m (CDNB) than the hGSTP1*A encoded protein (41). At high substrate (CDNB) concentration, V max of the reaction catalyzed by all three GST Pi proteins differed only modestly and was in the range reported in other studies of both tissue and recombinant GST Pi proteins (41,(45)(46)(47). K cat for CDNB was also similar for all three proteins, thus resulting in utilization ratios, K cat /K m , for GSTP1b-1c and GSTP1c-1c that were 3.3-and 4-fold lower, respectively, than that of GSTP1a-1a.…”
Section: Gstp1bsupporting
confidence: 81%
See 1 more Smart Citation
“…These results are similar to those in a previous report in which a recombinant GSTP1b-1b protein expressed from a cDNA obtained artificially by site-directed mutagenesis of hGSTP1*A, was shown to have a 4-fold higher K m (CDNB) than the hGSTP1*A encoded protein (41). At high substrate (CDNB) concentration, V max of the reaction catalyzed by all three GST Pi proteins differed only modestly and was in the range reported in other studies of both tissue and recombinant GST Pi proteins (41,(45)(46)(47). K cat for CDNB was also similar for all three proteins, thus resulting in utilization ratios, K cat /K m , for GSTP1b-1c and GSTP1c-1c that were 3.3-and 4-fold lower, respectively, than that of GSTP1a-1a.…”
Section: Gstp1bsupporting
confidence: 81%
“…Thermostability of Variant GST Pi Proteins-To further determine the effects of the amino acid changes on the variant GST Pi proteins, we compared the thermal stabilities of the enzymatic function of the three variant GST Pi proteins based in part on the expected differences in ␣-helix stability of the region of the GST Pi peptides containing the amino acid changes and on a previous study (41) that showed that a recombinant GST Pi enzyme corresponding to GSTP1b-1b, created by site-directed mutagenesis, was functionally more heat-stable than the parent enzyme. Each variant GST Pi protein was incubated at approximately 0.1 unit/ml at 45°C in phosphate-buffered saline (pH 7.2) in a water bath.…”
Section: Methodsmentioning
confidence: 99%
“…Polymorphisms in exon 5 (Ile105Val) and exon 6 (Ala114Val) of the GSTP1 gene were identified (Zimniak et al, 1994), and both affected codons lie in close proximity to the hydrophobic binding site of GSTP1. Moreover, polymorphism is known to change the properties of the enzyme (Ryberg et al, 1997).…”
Section: The Gstp1 Ile105val Polymorphism Is Not Associated With Suscmentioning
confidence: 99%
“…GSTP1 is involved in the inactivation of cigarette smoke carcinogens, such as BPDE, and other toxic constituents, such as acrolein [18], and GSTP1 is expressed in normal prostate cells [19]. An A to G transition at nucleotide 313 in exon 5 of the GSTP1 gene, which replaces isoleucine (Ile) at codon 105 with valine (Val) within the active site of the enzyme, is associated with reduced enzymatic activity for certain substrates and altered thermostability [20,21]. While some studies have found an association between prostate cancer and the codon 105 variant Val allele of GSTP1 (Val 105 ) [22][23][24], others have failed to find an association [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%